Uji Aktivitas Antihialuronidase In-Vitro dan Karakteristik Fisik Nanostructured Lipid Carrier Ekstrak Rimpang Langkuas laki-laki (Alpinia zerumbet) - Siti Umroh Noor; Dian Ratih Laksmitawati; Wahono Sumaryono (Fakultas Farmasi Universitas Pancasila, 2020)
The rhizome of Alpinia zerumbet (Pers.) B.L. Burtt & R.M. Sm) contains phenolic compounds, has antihyaluronidase activity which can reduce wrinkles on the skin. This study aims to determine the physical characteristics and antihyaluronidase activity of the nanostructured lipid carrier (NLC) of the Alpinia zerumbet rhizome extract in-vitro. Alpinia zerumbet rhizome powder (4/18) was extracted by kinetic maceration method using 70% ethanol solvent, concentrated with a rotary vacuum evaporator at 100 mm Hg at a temperature of ± 50oC. The resulting extract was prepared into NLC nanoparticles using polyethyleneglycol 8-beeswax, isopropyl myristate and acrylyl glucoside with the high speed homogenization-ultrasonication method. The resulting NLC extracts were characterized by nanoparticle size and morphology, polydispersity index and zeta potential and antihyaluronidase activity test was determined using the Sigma Aldrich and Tu & Tawata methods with slight modifications. The results of the NLC characterization of Alpinia zerumbet rhizome extract were 171.3 nm; 0.37; -26.8 mV; and spherical shape. The results of the antihyaluronidase activity of Alpinia zerumbet rhizome extract loaded NLC was 552.75 µg/mL. It was concluded that the Alpinia zerumbet rhizome extract loaded NLC can be formulated into topical preparations which have the potential to be antihyaluronidase with the ability to reduce wrinkles on the skin.